2016
DOI: 10.1111/ases.12350
|View full text |Cite
|
Sign up to set email alerts
|

Warmed, humidified CO2 insufflation benefits intraoperative core temperature during laparoscopic surgery: A meta‐analysis

Abstract: BackgroundIntraoperative hypothermia is linked to postoperative adverse events. The use of warmed, humidified CO2 to establish pneumoperitoneum during laparoscopy has been associated with reduced incidence of intraoperative hypothermia. However, the small number and variable quality of published studies have caused uncertainty about the potential benefit of this therapy. This meta‐analysis was conducted to specifically evaluate the effects of warmed, humidified CO2 during laparoscopy.MethodsAn electronic datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 46 publications
2
32
0
1
Order By: Relevance
“…Especially during more protracted laparoscopic operations, additional warming and humidification of the insufflation gas can lead to better maintenance of body temperature and avoidance of hypothermia in the second half of the operation and should therefore be used in addition. The authors of a recently published review also come to this conclusion 20 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Especially during more protracted laparoscopic operations, additional warming and humidification of the insufflation gas can lead to better maintenance of body temperature and avoidance of hypothermia in the second half of the operation and should therefore be used in addition. The authors of a recently published review also come to this conclusion 20 .…”
Section: Discussionmentioning
confidence: 86%
“…Operationshälfte führen und sollte daher zusätzlich verwendet werden. Zu diesem Schluss kommen die Autoren eines kürzlich publizierten Reviews 20 .…”
Section: Diskussionunclassified
“…To investigate the efficiency of gas coolants, the above tests were repeated for internal cooling mode with CO 2 gas. CO 2 was selected from among the applicable gas coolants for this study as this gas does not have any biocompatibility problem or infection risk according to previous studies and is suitable for using as coolant during bone drilling [18, 33, 34]. The use of CO 2 is also very common in medicine, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies reported that warmed humidified CO 2 insufflation in adult laparoscopic surgery could reduce pain and improve CBT. [1215,28] Few studies on this issue in the pediatric population yielded both positive and negative conclusions in relatively minor and nonprolonged laparoscopic surgeries. [29,30]…”
Section: Discussionmentioning
confidence: 99%